Recurrent amelanotic melanoma of nasal cavity: Biological variability and unpredictable behavior of mucosal melanoma. A case report - Damir Vučinić; Dag Zahirović; Dubravko Manestar; Ingrid Belac-Lovasić; Tamara Braut; Leo Kovač; Nives Jonjić; Gordana Zamolo (Clinics and Practice, 2019)
The aim of this report is to present a case of a patient with a recurrent nasal cavity amelanotic melanoma (AM), with emphasis on diagnosis and therapy options of this clinical entity. A 65-year-old female patient presented with pain in the right cheek region and nasal obstruction. In 2013, she was diagnosed with mucosal melanoma (MM) of the left nasal cavity. After endoscopic surgery and radiotherapy, the patient was followed by the oncology team. Five years after the initial diagnosis, rhinoscopy showed a tumorous formation in the right nasal cavity. The tumor mass was without black discoloration and was the same color as the surrounding nasal mucosa. Microscopic examination after biopsy of the tumor confirmed amelanotic MM. The patient underwent an additional endoscopic surgery. A complete standard diagnostic workup for MM found metastases in head and neck lymph nodes, on both sides. MMs of head and neck are uncommon malignancies. Unique biology of MM cells causes a high rate of recurrences. This report presents an example of recurrent AM of the nasal cavity, in treatment with checkpoint inhibitor (pembrolizumab), which could provide a good therapy option for patients with MM.